(Des)envolvimento local em regiões periféricas do capitalismo: limites e perspectivas no caso do estado do Amapá (1966 a 2006) - ABRANTES, Joselito Santos (Universidade Federal do Pará, 2019)
This thesis had as object evaluate if the changes on the scale of the promotion of regional public politics development, which got changed, starting on the national point of view until the local, resulted on improvements of the amapaense’s condition life, between the periods 1966 / 2006. Therefore, the study discusses a thematic which is coming more and more attention in the literature, been on the theoretical point of view or as result of the experiment observation: the analysis of quest of the public politics on the regional and local development of the federal Brazilian government, with the objective on Amapá state. So, analyze in which measure programs and projects of local development, as example DLIS (Desenvolvimento Local Integrado e Sustentável) and APL’s (Arranjos Produtivos Locais) carried out on Amapá has presented energy in common among the public scales of promotion of these politics. The thesis treats as one bibliographic analytic and empiric research of these politics, which became stronger in the beginning of 90’s decade, in the country, specifically on Amapá state. To get all that, it was made a concept theoretical, analytic and empiric able to demonstrate and elucidate some points that guided and directed the way of the regional and local sustainable and supported development on Amapá state, between 1966 and 2006. To the study carry on, besides the bibliographic and documental research, was realized the association of the quantitative and qualities researches predominated on your realization. Therefore, the exam of the results made by IDESAP (Indicador de Desenvolvimento Econômico e Social do Amapá) as the excepts economics and socials independents indicators analyzed, shows an evaluative and gradual process of the development on the Amapá state. Even we consider as very shy and modest the socioeconomic advances at Amapá, mainly in the beginning of the 90’s decades, characterized as a change of the point of view in terms of local/regional development, based on different opinions of that previous model, which should be called of centralizer or “exogenous”.